2012
DOI: 10.1016/j.ejvs.2012.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Endovenous Simulated Laser Experiments at 940 nm and 1470 nm Suggest Wavelength-Independent Temperature Profiles

Abstract: The results of our experiments show that wavelength on its own has not been demonstrated to be an important parameter to influence the temperature profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…In a study comparing 30-and 15-W power with a 940-nm diode laser, ablation rates, hyperpigmentation, and paresthesia were higher in the first group. Recanalization has been found to be associated with lower laser power [14]. Our current study revealed that a lower LEED with a 1470-nm laser could produce the same results.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a study comparing 30-and 15-W power with a 940-nm diode laser, ablation rates, hyperpigmentation, and paresthesia were higher in the first group. Recanalization has been found to be associated with lower laser power [14]. Our current study revealed that a lower LEED with a 1470-nm laser could produce the same results.…”
Section: Discussionsupporting
confidence: 86%
“…In a study comparing 810 nm with 980 nm, occlusion rates were the same, but there was less pain, bruising, and phlebitis with the latter. In another study comparing 1320-and 940-nm wavelengths, there was no difference in the ablation rates of GSV, but there was significantly less bruising and analgesic use (to relieve pain) in the first group [14]. In addition, longer wavelengths caused lower absorption in the blood, which led to fewer perforations on the vein wall [15].…”
Section: Discussionmentioning
confidence: 96%
“…With respect to this, a radial emitting fibre was developed and marketed. Theoretical calculations showed a reduction of the irradiation directly on the tissue surface compared to bare fibre techniques (34,35,43). Thus the irradiation value could be reduced below the ablation threshold of tissue (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that decreasing the pullback speed (2 mm/s) and increasing the power (up to 14 W) both caused higher maximal temperatures. The use of different laser wavelengths (940 or 1470 nm) did not influence the temperature profile (53).…”
Section: The Veinsmentioning
confidence: 90%